2016
DOI: 10.1136/gutjnl-2015-310297
|View full text |Cite
|
Sign up to set email alerts
|

Titanium dioxide nanoparticles exacerbate DSS-induced colitis: role of the NLRP3 inflammasome

Abstract: ObjectiveWestern lifestyle and diet are major environmental factors playing a role in the development of IBD. Titanium dioxide (TiO2) nanoparticles are widely used as food additives or in pharmaceutical formulations and are consumed by millions of people on a daily basis. We investigated the effects of TiO2 in the development of colitis and the role of the nucleotide-binding oligomerisation domain receptor, pyrin domain containing (NLRP)3 inflammasome.DesignWild-type and NLRP3-deficient mice with dextran sodiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
200
4
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 253 publications
(219 citation statements)
references
References 54 publications
11
200
4
4
Order By: Relevance
“…The total uptake of nanoparticles by patients is at an average of 2.5 mg per person and day but may increase up to 40 mg. Interestingly, there is a high content of titanium dioxide in coffee whitener, pastry (due to the flour content), toothpaste, chewing gum or drug preparations. We could demonstrate that titanium dioxide activates the immune system [91] . This activation is mainly mediated via a protein complex called the inflammasome.…”
Section: Identification Of Pathomechanismsmentioning
confidence: 99%
See 3 more Smart Citations
“…The total uptake of nanoparticles by patients is at an average of 2.5 mg per person and day but may increase up to 40 mg. Interestingly, there is a high content of titanium dioxide in coffee whitener, pastry (due to the flour content), toothpaste, chewing gum or drug preparations. We could demonstrate that titanium dioxide activates the immune system [91] . This activation is mainly mediated via a protein complex called the inflammasome.…”
Section: Identification Of Pathomechanismsmentioning
confidence: 99%
“…The effector subunit is caspase-1 that cleaves prointerleukin 1β (IL-1β) and to the mature IL-1β and pro-IL-18 that can then be secreted. We found that in cell culture titanium dioxide was a strong activator of the inflammasome and subsequently induced IL-1β release [91] . In a mouse model, there was an aggravation of colitis induced by dextran sodium sulfate in the presence of titanium dioxide in the diet [91] .…”
Section: Identification Of Pathomechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of NF-κB activation, macrophages start to secrete a panel of pro-inflammatory cytokines (TNFα, IL-1β, IL-6, IL-8, shown that phagocytosis of titanium nano-and microparticles up-regulates the expression of TNFα, IL-1β and IL-6 on both mRNA and protein levels (Beidelschies et al, 2008, Luo et al, 2016, Minematsu et al, 2007, Naganuma et al, 2016, Pajarinen et al, 2013, Rakshit et al, 2006, Ruiz et al, 2016, Valles et al, 2006, Yazdi et al, 2010. Additionally, the inflammasome protein NLPR3 which is responsible for IL-1β and IL-18 activation (Martinon et al, 2002), is also up-regulated in macrophages by titanium (Naganuma et al, 2016, Ruiz et al, 2016, Yazdi et al, 2010.…”
Section: Immune Response To Titaniummentioning
confidence: 99%